2015
DOI: 10.1111/jvh.12390
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA‐155 correlates positively with the expression of Toll‐like receptor 7 and modulates hepatitis B virus via C/EBP‐β in hepatocytes

Abstract: Effective recognition of viral infection and successive activation of antiviral innate immune responses are vital for host antiviral defence, which largely depends on multiple regulators, including Toll-like receptors (TLRs) and microRNAs. Several early reports suggest that specific TLR-mediated immune responses can control hepatitis B virus (HBV) replication and express differentially with disease outcome. Considering the versatile function of miR-155 in the TLR-mediated innate immune response, we aimed to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 45 publications
5
36
0
Order By: Relevance
“…Previous reports have shown that TLR4 expression remains down regulated in HepG2.2.15 cells compared to HepG2 cells[14]. This was re-affirmed in our study (Figure 1A).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Previous reports have shown that TLR4 expression remains down regulated in HepG2.2.15 cells compared to HepG2 cells[14]. This was re-affirmed in our study (Figure 1A).…”
Section: Resultssupporting
confidence: 92%
“…In an attempt to identify the pathway that is responsible for viral elimination, different chemical inhibitors (PDTC for NF-κB, LY294002 for PI3K, SP600125 for JNK and SB203580 for p38) were used, after which LPS was used to stimulate the TLR4 signaling pathway. These chemical blockers block MAPKs and NF-κB activation specifically, and have been used in several studies previously for pathway analysis[14,17]. Interestingly, on blocking NF-κB with its inhibitor eliminated the anti-viral role of TLR4.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have showed that TLR7 mRNA expression is highly compromised in HBV replicating HepG2.2.15 cells when compared to the HepG2 cells [9]. It is believed that HBV represses the innate immune response during a natural infection.…”
Section: Resultsmentioning
confidence: 99%
“…The maintenance and plating of hepatoblastoma cell lines HepG2 and HepG2.2.15 was done as described previously [9]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation